2020
DOI: 10.1007/s13364-020-00524-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal partitioning by felids, dholes and their potential prey in northern Laos

Abstract: Temporal partitioning can allow sympatric carnivores to coexist, especially if overlap of other resources is high. Using camera trap data from 2013 to 2017, we investigated the temporal partitioning of a community of wild felids and a canid in Nam Et–Phou Louey National Protected Area, Laos, to determine the extent to which temporal avoidance might be facilitating coexistence of similarly sized carnivores. We also investigated temporal overlap of these carnivore species and their presumed main prey, to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
(84 reference statements)
2
13
0
Order By: Relevance
“…The study results from the spatialtemporal separation of dhole and clouded leopard (Neofelis nebulosa), the largest carnivore in Nam Et-Phou Louey National Protected Area in Laos, showed the least temporal overlap. It also revealed that dhole had significant temporal-overlap activities with potential wild prey (Rasphone et al 2020). Vinitpornsawan and Fuller (2020) studied the spatialtemporal utilization of habitat of tiger, leopard, dhole, and their preys in the Western Thungyai Naresuan Wildlife Sanctuary during 2010-2012 using camera traps.…”
Section: Introductionmentioning
confidence: 99%
“…The study results from the spatialtemporal separation of dhole and clouded leopard (Neofelis nebulosa), the largest carnivore in Nam Et-Phou Louey National Protected Area in Laos, showed the least temporal overlap. It also revealed that dhole had significant temporal-overlap activities with potential wild prey (Rasphone et al 2020). Vinitpornsawan and Fuller (2020) studied the spatialtemporal utilization of habitat of tiger, leopard, dhole, and their preys in the Western Thungyai Naresuan Wildlife Sanctuary during 2010-2012 using camera traps.…”
Section: Introductionmentioning
confidence: 99%
“…activity overlap, biomass consumed, camera-trapping, dietary overlap, Felis chaus, open dry deciduous forests, Prionailurus bengalensis, Southeast Asia, species interactions, two-species occupancy modeling Alternatively, when overlap levels of spatial niche and food resources are high, temporal partitioning can occur, whereby subordinate species adjust their activity patterns to reduce encounters and facilitate coexistence with a dominant competitor. Low overlap of activity patterns has been shown to exist between small felid species in Southeast Asia (Kamler, Inthapanya, et al, 2020;Lynam et al, 2013;McCarthy et al, 2015;Mukherjee et al, 2019;Rasphone et al, 2020) and in other regions of the world (Leonard et al, 2020;Lucherini et al, 2009;Nagy-Reis et al, 2019), indicating this strategy also is used to enable coexistence between similarly sized felids.…”
Section: Introductionmentioning
confidence: 99%
“…l Allayarov (1964) (includes contents from 6 stomachs). almost strictly nocturnal (Grassman et al, 2005;Kamler, Inthapanya, et al, 2020;Lynam et al, 2013;Mukherjee et al, 2019;Rasphone et al, 2020), which could facilitate temporal partitioning between these species if jungle cats are more diurnal. Jungle cats are considerably taller than leopard cats (Francis, 2019) and twice the body weight; consequently, jungle cats should behaviorally dominate leopard cats, although their interactions have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…consisted of two large felids, tiger (Panthera tigris) and leopard (P. pardus), together with the "standard four" medium and small felids: clouded leopard (Neofelis nebulosa), Asian golden cat (Catopuma temminckii), marbled cat (Pardofelis marmorata), and leopard cat (Prionailurus bengalensis; Duckworth et al 2014). Several studies have examined the mechanisms that allow such a diverse felid community to coexist, and have concluded that temporal partitioning and dietary partitioning likely help to facilitate their coexistence (Mukherjee et al 2019;Nagy-Reis et al 2019;Kamler et al 2020;Rasphone et al 2020). Additionally, smaller felid species may sometimes, but not always, behaviorally avoid larger felid species (McDougal et al 1988;Horne et al 2009;Foster et al 2013;Rostro-García et al 2015, 2021, thereby further facilitating their coexistence.…”
Section: Introductionmentioning
confidence: 99%